2021
DOI: 10.1093/geroni/igab046.3300
|View full text |Cite
|
Sign up to set email alerts
|

Aging Men and Masculinity Ideologies: Variance Composition of the MRNS-BF and Measurement Invariance by Men's Age

Abstract: Medicare’s Hospital Readmissions Reduction Program (HRRP) places disproportionate penalties on hospitals serving populations with complex medical and social needs. Without measures to identify the social need intensity of populations cared for by these hospitals, the HRRP cannot account for these risk factors, leading to burdensome penalties that may inadvertently hinder the ability of such hospitals to care for vulnerable populations. The objective of this study is to characterize the social need intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The most significant difference in both cases was between the youngest and the oldest age groups, with the 60+ group showing the highest levels of endorsement of both masculine and anti-effeminacy norms. These findings reflect some of the literature, where older cohorts emphasised avoiding femininity more than younger cohorts did (Thompson & Levant, 2021). However, they contradict findings in other studies suggesting that gender norms become less rigid with age (Herreen et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The most significant difference in both cases was between the youngest and the oldest age groups, with the 60+ group showing the highest levels of endorsement of both masculine and anti-effeminacy norms. These findings reflect some of the literature, where older cohorts emphasised avoiding femininity more than younger cohorts did (Thompson & Levant, 2021). However, they contradict findings in other studies suggesting that gender norms become less rigid with age (Herreen et al, 2021).…”
Section: Discussionsupporting
confidence: 69%
“…For example, Thompson and Levant (2021) found that endorsement of traditional norms differed between age cohorts, with older cohorts emphasising the importance of avoiding femininity, and younger cohorts emphasising gender equality.…”
Section: Introductionmentioning
confidence: 99%